2022
DOI: 10.1029/2022ja031005
|View full text |Cite
|
Sign up to set email alerts
|

On the Spatial Structure and Zonal Drift of Low Latitude E Region Irregularity Patches Over Hainan

Abstract: All‐sky radar measurements provide a unique capability to resolve the spatial structure of E region irregularities over a large zonal region. With the all‐sky radar interferometry observations at Ledong (18.4°N, 109.0°E) in Hainan, China, the spatial structure and zonal drift of low latitude E region field‐aligned irregularities (FAIs) over a large region are statistically investigated for the first time. It is revealed that the E region FAIs, including both the continuous and quasi‐periodic (QP) types shown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…In previous studies, the spatially separated structures of QP‐type E‐region irregularities were presumed to be modulated by gravity waves (e.g., Sun et al., 2023; Yokoyama et al., 2004). However, any QP structures could not necessarily represent the existence of a modulating wave.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, the spatially separated structures of QP‐type E‐region irregularities were presumed to be modulated by gravity waves (e.g., Sun et al., 2023; Yokoyama et al., 2004). However, any QP structures could not necessarily represent the existence of a modulating wave.…”
Section: Discussionmentioning
confidence: 99%
“…Based on numerical simulations, it was suggested that the E s layer accumulated by wind shears could be deeply modulated by the propagating gravity waves, and the polarization electric field due to the distorted E s layer could produce wavelike patterns of plasma density (e.g., Huang & Kelley, 1996; Ogawa et al., 2002; Yokoyama et al., 2003). However, such mechanisms were usually proposed to account for generating the spatially separated structures of QP‐type E‐region irregularities (e.g., Sun et al., 2023). It is not clear whether it could be employed to explain the wavelike E‐region irregularity structures elongating up to 250 km in the present case or not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations